On the Link Between Emotionally Driven Impulsivity and Aggression: Evidence From a Validation Study on the Dutch UPPS-P. (June 2018) - Bousardt, A. M. C.; Noorthoorn, E. O.; Hoogendoorn, A. W.; Nijman, H. L. I.; Hummelen, J. W.
The UPPS-P seems to be a promising instrument for measuring different domains of impulsivity in forensic psychiatric patients. Validation studies of the instrument however, have been conducted only in student groups. In this validation study, three groups completed the Dutch UPPS-P: healthy student ( N = 94) and community ( N = 134) samples and a forensic psychiatric sample ( N = 73). The five-factor structure reported previously could only be substantiated in a confirmatory factor analysis over the combined groups but not in the subsamples. Subgroup sample sizes might be too small to allow such complex analyses. Internal consistency, as assessed by Cronbach's alpha, was high on most subscale and sample combinations. In explaining aggression, especially the initial subscale negative urgency (NU) was related to elevated scores on self-reported aggression in the healthy samples (student and community). The current study is the second study that found a relationship between self-reported NU and aggression highlighting the importance of addressing this behavioural domain in aggression management therapy.